Family farms from Romania Nord Vest Region in the context of the rural sustainable development - Maria Mortan; Vincenţiu Vereş; Leonina Baciu; Patricia Raţiu (CES Working Papers, 2018)
This paper analyses the extent to which aspects contributing to sustainable development are integrated at family farms level. The present research aims to inventory the state of family farms from the Nord Vest development region1 from Romania, to see how they can contribute to the sustainable development of the area. Another objective is to investigate the availability of the family farm to develop and to identify the variables that can influence this desire, given its role in the existence of the Romanian village. As it was noted from the literature review, family farms have different characteristics from one country to another and even from one area to another, thus requiring different approaches. The characteristics revealed at the level of family farms from the Nord Vest Region outline a low economic viability, which indicates a low probability of economic development in the absence of coherent policies to support them directly.
Keywords: 330; family farms; sustainable rural development; economic viability; Nord-Vest Region